Contribution to Local Economic Development in the light of a Chinese subsidiary company in Hungary - Liu Weilong (2017)
With the deepening of reform and opening up, especially after 2010, China's participation in international organizations and processing of international affairs has increased rapidly and has had a positive and far-reaching impact on the world economy. Among them, China has proposed two important external economic strategies, named "Going Global" strategy and "One Belt One Road" Policy. In response to the call of the country, more and more China's leading companies were constantly investing in foreign markets and building overseas factories and branches to expand the influence of Chinese companies during the last 10 years. This also could change the past impression "made in China" to a new impression of "created in China". Chinese enterprises are also committed to developing the investment countries’ economy, improving people's living standards and promoting the exchange and integration of China-Foreign cultures. The Wanhua-BC company in my thesis is a more convincing example. Firstly, I will introduce the general situation of China's Wanhua Group and Hungary's BC company. And then explain the contribution of Chinese enterprises to Hungary's economy, culture and education in the exact region. Because of it, I also think of other cooperation between China and Hungary, such as HUAWEI's investment in Hungary. Finally, I will introduce China's "Going Global" strategy and "One Belt One Road" Policy, and make some own thinking. Key Words: "Going Global" strategy, "One Belt One Road" Policy, reform and opening up, investment.